Water reuse : (McGraw-Hill, 2007)
An Integrated Approach to Managing the World's Water Resources Water Reuse: Issues, Technologies, and Applicationsequips water/wastewater students, engineers, scientists, and professionals with a definitive account of the latest water reclamation, recycling, and reuse theory and practice. This landmark textbook presents an integrated approach to all aspects of water reuse _ from public health protection to water quality criteria and regulations to advanced technology to implementation issues. Filled with over 500 detailed illustrations and photographs,Water Reuse: Issues, Technology, and Applicationsfeatures: In-depth coverage of cutting-edge water reclamation and reuse applications Current issues and developments in public health and environmental protection criteria, regulations, and risk management Review of current advanced treatment technologies, new developments, and practices Special emphasis on process reliability and multiple barrier concepts approach Consideration of satellite and decentralized water reuse facilities Consideration of planning and public participation of water reuse